Concepts: neither Representations nor Abilities but Rules - Federico Castellano (Principia: An International Journal of Epistemology, 2018)
Philosophers have always tried to explain what concepts are. Currently, most neo- Fregean philosophers identify concepts with abilities peculiar to cognitive agents. Philosophers who defend a psychological view, in contrast, identify concepts with representations located in the mind. In this paper, I argue that concepts should be understood neither in terms of mental representations nor in terms of abilities. Concepts, I argue, are rules for sorting an inferring. To support this, I follow Ginsborg’s Kantian conception of concepts. Nevertheless, unlike Ginsborg, I provide an explanation of the cognitive relationship between concepts and thinkers that presupposes no linguistic awareness of any normative concept. In doing so, a dispositional approach to the normativity of concepts is proposed.